Somatic gene mutation patterns and burden influence outcomes with enasidenib in relapsed/refractory IDH2-mutated AML - Risueño, A; See, WL; Bluemmert, I; de Botton, S; DiNardo, CD; Fathi, AT; Schuh, AC; Montesinos, P; Vyas, P; Prebet, T; Gandhi, A; Hasan, M (Elsevier, 2024)
Limited treatment options are available for patients with relapsed/refractory acute myeloid leukemia (R/R AML). We recently reported results from the phase 3 IDHENTIFY trial (NCT02577406) showing improved response rates and event-free survival with enasidenib monotherapy compared with conventional care regimens (CCR) in heavily pretreated, older patients with late-stage R/R AML bearing IDH2 mutations. Here we investigated the prognostic impact of mutational burden and different co-mutation patterns at study entry within the predominant IDH2 variant subclasses, IDH2-R140 and IDH2-R172. The prognostic relevance of these variants is well documented in newly diagnosed AML, but data are lacking in R/R AML. In this large R/R AML patient cohort, targeted next-generation sequencing at baseline (screening) revealed distinct co-mutation patterns and mutational burden between subgroups bearing different IDH2 variants: variant IDH2-R140 was associated with greater mutational burden and was enriched predominantly with poor-risk mutations, including FLT3, RUNX1, and NRAS, while variant IDH2-R172 was associated with lower mutational burden and was preferentially co-mutated with DNMT3A. In multivariable analyses, RAS and RTK pathway mutations were significantly associated with decreased overall survival, after adjusting for treatment arm, IDH2 variant, and mutational burden. Importantly, enasidenib-mediated survival benefit was more pronounced in patients with IDH2-R172 variants.